2006
DOI: 10.1145/1141911.1142018
|View full text |Cite
|
Sign up to set email alerts
|

Real-time video abstraction

Abstract: Figure 1: Abstraction examples. Original: Snapshots of a guard in Petra (left) and two business students (right). Abstracted: After several bilateral filtering passes and with DoG-edges overlayed. Quantized: Luminance channel soft-quantized to 12 bins (left) and 8 bins (right). Note how folds in the clothing and other image details are emphasized (stones on left and student's shadows on right). AbstractWe present an automatic, real-time video and image abstraction framework that abstracts imagery by modifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
111
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 419 publications
(111 citation statements)
references
References 25 publications
0
111
0
Order By: Relevance
“…Another example is image and video stylization and abstraction [DeCarlo and Santella 2002;Winnemöller et al 2006]. Here the details are discarded, while the base layer is further processed to achieve a stylized look.…”
Section: Introductionmentioning
confidence: 99%
“…Another example is image and video stylization and abstraction [DeCarlo and Santella 2002;Winnemöller et al 2006]. Here the details are discarded, while the base layer is further processed to achieve a stylized look.…”
Section: Introductionmentioning
confidence: 99%
“…In doing so, they also drew conclusions with respect to some of Salesin's challenges such as the artistic Turing test by examining techniques that largely did not pass at the time. Evaluation work more closely aligned with Salesin's visual communication challenge was proposed by Gooch et al [43] and Winnemöller et al [164] in their portrait abstractions. It was shown that abstracted faces were more quickly recognized than photorealistic imagery, implying improved comprehension through IB-AR.…”
Section: Discussionmentioning
confidence: 99%
“…A fully automatic pipeline for the stylization of cartoon renderings based on images and videos was first proposed in the seminal work by Winnemöller et al [164]. Their pipeline employs the bilateral and difference of Gaussians (DoG) filter and contains several influential ideas that other researchers later built upon.…”
Section: Bilateral Filter and Difference Of Gaussiansmentioning
confidence: 99%
See 2 more Smart Citations